Checklist of arachnids in the highlands area of Gunung Ledang National Park, Johor, Malaysia - Irham Razak,; Dzulhelmi Muhammad Nasir,; Macdey Jengkeng,; Aliff Ariff,; Danial Dean,; Mohamad Aqmal-Naser,; Amirrudin Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mount Ledang National Park is one of the famous hiking spots in Johor, Malaysia which is the 1,276-meter peak of Mount Ledang. Between 21st-25th August 2023, a visual encounter survey method was conducted from 0900-1700 and 2000-2300 hours to document the Arachnid species that occur at 900-1200 meters above sea level. In total, 27 species from 14 families of arachnids were recorded from two orders; Araneae and Opiliones. Clustering analysis showed that Pendeta Trail and Batu Hampar Trail have 70% similar species composition, and Telekom Trail has a 37% difference between the two trails. Extrapolation of the species accumulation curve shows an increasing trend and has not reached an asymptote. The analyses on estimated species richness revealed that Arachnid species richness was at a minimum of 32 species, and a maximum of 47 species. Interestingly, a new record of tube trapdoor spider, Damarchus workmanii, and an undescribed Psednocnemis tarantula species found from this survey shows the importance of preserving the highland areas of this national park which remains to be further explored.